Sleep-related traits and attention-deficit/hyperactivity disorder comorbidity: Shared genetic risk factors, molecular mechanisms, and causal effects. (26th November 2021) - Carpena, Marina Xavier; Bonilla, Carolina; Matijasevich, Alicia; Martins-Silva, Thais; Genro, Julia P.; Hutz, Mara Helena; Rohde, Luis Augusto; Tovo-Rodrigues, Luciana
Abstract: Objectives: To evaluate the shared genetic components, common pathways and causal relationship between ADHD and sleep-related phenotypes Methods: We used the largest genome-wide association summary statistics available for attention-deficit/hyperactivity disorder (ADHD) and various sleep-related phenotypes (insomnia, napping, daytime dozing, snoring, ease getting up, daytime sleepiness, sleep duration and chronotype). We estimated the genomic correlation using cross-trait linkage disequilibrium score regression (LDSR) and investigated the potential common mechanisms using gene-based cross-trait metanalyses and functional enrichment analyses. The causal effect was estimated using two-sample Mendelian randomisation (TSMR), using the inverse variance weighted method as the main estimator. Results: A positive genomic correlation between insomnia, daytime napping, daytime dozing, snoring, daytime sleepiness, short and long sleep duration, and ADHD was observed. Insomnia, daytime sleepiness, and snoring shared genes with ADHD, that are involved in neurobiological functions and regulatory signalling pathways. The TSMR supported a causal effect of insomnia, daytime napping, and short sleep duration on ADHD, and of ADHD on long sleep duration and chronotype. Conclusion: Comorbidity between sleep phenotypes and ADHD may be mediated by common genetic factors that play an important role in neuronal signalling pathways. A causal effect of sleep disturbances and short sleep duration on ADHD reinforced their role as predictors of ADHD.